2020
DOI: 10.1136/ijgc-2019-000849
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of lymphovascular space invasion for stage IA1 and IA2 cervical cancer

Abstract: BackgroundData regarding the prognostic significance of lymphovascular space invasion (LVSI) for stage IA1 and IA2 cervical cancer are limited. Specifically, the role of LVSI as an independent risk factor for mortality in stage IA disease has not been shown.ObjectiveWe examined the association between LVSI and nodal metastases and survival for women with stage IA1 and IA2 cervical cancer.Study DesignWe used the National Cancer Database to identify patients with stage IA adenocarcinoma or squamous carcinoma of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Lymphovascular space invasion (LVSI) refers to the presence of cancer cell clusters in the vascular and/or lymphatic lumen (2). LVSI increases the risk of lymph node metastases (LNM), which is an independent high-risk factor for tumor recurrence and influences treatment methods (3)(4)(5). Studies have shown that LVSI is associated with decreased survival rates in women with stage IA2 (5), IB, and II CC [defined according to the Federation International of Gynecology and Obstetrics (FIGO)] (3,6).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lymphovascular space invasion (LVSI) refers to the presence of cancer cell clusters in the vascular and/or lymphatic lumen (2). LVSI increases the risk of lymph node metastases (LNM), which is an independent high-risk factor for tumor recurrence and influences treatment methods (3)(4)(5). Studies have shown that LVSI is associated with decreased survival rates in women with stage IA2 (5), IB, and II CC [defined according to the Federation International of Gynecology and Obstetrics (FIGO)] (3,6).…”
Section: Introductionmentioning
confidence: 99%
“…LVSI increases the risk of lymph node metastases (LNM), which is an independent high-risk factor for tumor recurrence and influences treatment methods (3)(4)(5). Studies have shown that LVSI is associated with decreased survival rates in women with stage IA2 (5), IB, and II CC [defined according to the Federation International of Gynecology and Obstetrics (FIGO)] (3,6). Satellite LVSIs also significantly increase the risk of death and recurrence (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of recurrence after initial surgery is evaluated by pathological criteria such as lymph node metastasis, LVSI, depth of stromal invasion, parametrial invasion, tumor size, and positive surgical margins. 14,15 According to a recent report, 16 among patients with stage IA1 and IA2 disease, 10.5% and 18.8% had LVSI. Wenzel et al 12 reported that for tumors with an invasion depth of ≤5 mm and a horizontal spread of >7 mm, the incidence of LVSI and lymph node metastasis was 26.9% and 3.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it guides postoperative treatment planning in early cervical cancer. [ 2 ] Pelvic lymphadenectomy procedure as well as radical hysterectomy procedure is routinely used as the treatment in order to avoid the under diagnosis of lymph node metastasis. From the past to the present, removal of pelvic lymph nodes has shown poor clinical effects, including nerve damage, lymphedema and lymphocyst formation, contributing to increased operative time, blood loss.…”
Section: Introductionmentioning
confidence: 99%